Preparation method of molybdenum disulfide nanofiber piezoelectric material

The solution replacement method is used to prepare molybdenum disulfide nanofiber piezoelectric materials, which solves the interface combination and dispersion of nanofiber materials and molybdenum disulfide nanocrystal composite materials, and realizes high-performance nanofiber piezoelectric materials, improving the mechanics of the materials and piezoelectric properties have expanded the application fields.

CN119306975APending Publication Date: 2025-01-14BEIJING INFORMATION SCI & TECH UNIV
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
CN202411420603.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Nanofiber materials and molybdenum disulfide nanocrystal composites have problems such as intimate interface bonding and uneven dispersion, making it difficult to achieve performance complementarity and performance improvement.

Method used

Molybdenum disulfide nanofiber piezoelectric material was prepared by solution replacement method. By combining polyvinyl alcohol, N-methylpyrrolidone, anhydrous ethanol and deionized water, ball milling, heating and stirring, cooling and curing, solvent removal, and ultrasonic uniformity. Distribution and other steps to form a stable nanofiber structure to ensure uniform dispersion of molybdenum disulfide nanocrystals in the nanofibers.

Benefits of technology

The high specific surface area and high voltage electrical properties of molybdenum disulfide nanofiber piezoelectric materials are achieved, the mechanical strength and cyclic stability of the material are improved, the demand for piezoelectric properties in different fields is met, and the application scope is broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306975A_ABST
    Figure CN119306975A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a molybdenum disulfide nanofiber piezoelectric material. By optimizing dispersing, mixing and forming processes, the molybdenum disulfide nanocrystals can be uniformly dispersed in a nanofiber matrix, and tight compounding of the molybdenum disulfide nanocrystals and a nanofiber material is realized, so that the composite material with high specific surface area and high piezoelectric property is prepared. According to the preparation method, the problems that molybdenum disulfide nanocrystals are poor in stability and difficult to form in application are solved, the electrical property of the composite material is remarkably improved through introduction of the nanofiber material, the application range of the composite material is widened, and particularly, a new preparation method and thought are provided for application of a two-dimensional material in the field of flexible electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano piezoelectric material preparation, and specifically relates to a method for preparing molybdenum disulfide nanofiber piezoelectric material. Background Art

[0002] In modern science and technology, nanomaterials have always attracted much attention due to their unique physical, chemical and biological properties, and are widely used in many fields such as energy, environment, biomedicine, etc. Among them, molybdenum disulfide (MoS2), as a typical two-dimensional nanomaterial, has become the focus of research and application in the scientific community due to its excellent electrical, optical and mechanical properties.

[0003] MoS2 materials have a variety of crystal structures, the most common of which are 1T and 2H phases. These two structures have significant differences in physical properties and applications. 1T phase MoS2 has the electronic structure of a metallic phase, while 2H phase is a typical semiconductor with a band gap of about 1.2 eV. This difference makes different phases of MoS2 show completely different performance and application potential in electricity, optics and catalysis.

[0004] The application of nanofiber materials covers many fields. In the energy field, nanofiber materials are used to prepare flexible electrodes and batteries, which improve the energy density and cycle stability of batteries. In the environmental field, nanofiber materials are used in sewage treatment, gas adsorption and catalyst carriers, and have good adsorption performance and catalytic activity. In the biomedical field, nanofiber materials are used in tissue engineering, drug delivery and biosensing, and have good biocompatibility and bioactivity.

[0005] The combination of nanofiber materials and MoS2 nanocrystals can expand the application field of MoS2 nanocrystals and give them new functions and properties. For example, by combining MoS2 nanocrystals with nanofiber materials, composite materials with high specific surface area and excellent photoelectric properties can be prepared for use in photocatalysis, optoelectronic devices and other fields. In addition, nanofiber materials can also be used as carriers to stabilize the structure of MoS2 nanocrystals and improve their stability and cycle performance in applications.

[0006] However, the composite of nanofiber materials and molybdenum disulfide nanocrystals still faces many technical bottlenecks. Composite materials prepared by traditional methods often have problems such as loose interface bonding and uneven dispersion. In addition, how to effectively introduce molybdenum disulfide nanocrystals while maintaining the original excellent properties of nanofiber materials to achieve performance complementarity and improvement is also a major challenge in current research.

[0007] In view of the above problems, the present invention proposes a method for preparing a piezoelectric material of molybdenum disulfide nanofibers, which aims to achieve a close compound of molybdenum disulfide nanocrystals and nanofiber materials through an innovative preparation process, thereby preparing a composite material with a high specific surface area and high piezoelectric performance. This invention not only solves the problems of poor stability and difficult molding of molybdenum disulfide nanocrystals in applications, but also significantly improves the piezoelectric properties of the composite material through the introduction of nanofiber materials, thereby broadening its application range.

[0008] Specifically, the present invention optimizes the dispersion, mixing and molding processes to enable the molybdenum disulfide nanocrystals to be uniformly dispersed in the nanofiber matrix to form a stable layered structure. At the same time, the high specific surface area and good mechanical properties of the nanofiber material are utilized to effectively improve the mechanical strength and cycle stability of the composite material. In addition, by adjusting the content and distribution of the molybdenum disulfide nanocrystals, the present invention also achieves precise control of the piezoelectric properties of the composite material, so that it can meet the requirements for the performance of piezoelectric materials in different fields.

[0009] Therefore, the preparation method of a molybdenum disulfide nanofiber piezoelectric material provided by the present invention not only solves the bottleneck problem faced in current research, but also provides strong support for realizing the high performance, multifunctionality and wide application of molybdenum disulfide nanomaterials. Summary of the invention

[0010] The purpose of the present invention is to overcome the problems existing in the prior art, combine the advantages of nanofiber technology, and provide a method for preparing molybdenum disulfide nanofiber piezoelectric material. The solution replacement method is used to synthesize a highly stable nanofiber structure, which can effectively solve the application of molybdenum disulfide piezoelectricity in high-precision integrated devices in the prior art.

[0011] To achieve the above-mentioned purpose, the present invention provides a method for preparing a molybdenum disulfide nanofiber piezoelectric material, characterized in that a composite solution of the molybdenum disulfide nanofiber piezoelectric material is prepared by solution replacement using polyvinyl alcohol, molybdenum disulfide, N-methylpyrrolidone, anhydrous ethanol and deionized water as raw materials.

[0012] Preferably, the molybdenum disulfide in the molybdenum disulfide nanofiber composite solution is a 100 nm two-dimensional powder material, and the preparation method of the molybdenum disulfide nanofiber composite solution is as follows:

[0013] (1) mixing molybdenum disulfide powder and polyvinyl alcohol (PVA) powder uniformly by ball milling in a ratio of 1:1 to 8:1;

[0014] (2) adding the mixed powder of step (1) into N-methylpyrrolidone (NMP), heating and stirring at 120° C. for 2 h, wherein the mass ratio of NMP to PVA is 10:1, to obtain molybdenum disulfide gel;

[0015] (3) pouring the molybdenum disulfide gel obtained in step (2) into a mold made of an inorganic polymer colloidal material obtained by condensation of silicate, and cooling it in an environment of -25°C for more than 6 hours, so as to solidify the gel at low temperature and form a nanofiber material with a certain shape;

[0016] (4) placing the cooled molybdenum disulfide gel obtained in step (3) in an anhydrous ethanol solution for more than 6 hours to allow ethanol to displace NMP. This step is to remove NMP in the gel to avoid interference with subsequent treatments;

[0017] (5) placing the gel obtained in step (4) in deionized water for 24 hours to allow the deionized water to displace the ethanol, in order to further remove the organic solvent in the gel to obtain a purer nanofiber material;

[0018] (6) taking the supernatant after the replacement in step (5), pouring it into a centrifuge tube, and centrifuging it at 4000 rpm for 40 minutes to separate the impurities and unreacted raw materials in the nanofiber material by centrifugation;

[0019] (7) sonicating the solution after centrifugation in step (6) for 2 h to allow the MoS2 nanocrystals to fully grow into the fiber knots. The key to this step is to utilize the oscillation effect of ultrasound to promote the uniform distribution and growth of MoS2 nanocrystals in the nanofibers;

[0020] (8) The solution after ultrasound was taken out and observed by TEM. The obvious fiber structure embedded in the quantum morphology can be observed. The material was used to prepare a simple piezoelectric film sensor and the piezoelectric coefficient d was obtained by testing. 33 It is about 345pC / N; PFM test on this material shows good piezoelectric domain structure and obvious piezoelectric effect; test in sensor test system shows good sensitivity.

[0021] Preferably, the molybdenum disulfide is 1g, the polyvinyl alcohol powder is 1g, and the N-methylpyrrolidone is 10ml.

[0022] The principle of the present invention is that when molybdenum disulfide nanocrystals are mixed with PVA aqueous solution, a strong interaction is generated between the two. This interaction is mainly achieved through hydrogen bonds and van der Waals forces, wherein the hydroxyl functional groups of PVA form hydrogen bonds with the surface of molybdenum disulfide nanocrystals, ensuring the uniform dispersion of the nanocrystals in the PVA hydrogel. At the same time, the presence of van der Waals forces further stabilizes this dispersion state, providing a stable external structure for the molybdenum disulfide nanocrystal piezoelectric material.

[0023] The advantages and benefits of the present invention are that the introduction of molybdenum disulfide nanocrystals brings multiple advantages to PVA hydrogel. First, in terms of performance, molybdenum disulfide nanocrystals significantly improve the electrical properties of PVA hydrogel, and enhance its electrical transmission capacity and stability. Secondly, the structural stability is also improved. The special structure formed by molybdenum disulfide in PVA hydrogel enhances the mechanical properties of the gel, which helps to maintain the long-term stable operation of the device. From the perspective of material preparation, this composite material has a very strong controllability. By adjusting the addition amount and dispersion state of molybdenum disulfide nanocrystals, the structure and properties of PVA hydrogel can be precisely regulated to meet the needs of different applications. It is worth mentioning that this composite material also has environmentally friendly characteristics. PVA hydrogel itself is an environmentally friendly material, and the combination with molybdenum disulfide nanocrystals further enhances its environmental performance, which is in line with the development trend of green chemistry and materials science. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 The attached figure is a TEM morphology image of the molybdenum disulfide nanofiber piezoelectric material prepared in Example 1.

[0026] Figure 2 The attached figure is a piezoelectric effect sensitivity diagram of the molybdenum disulfide nanofiber piezoelectric material in Example 1.

[0027] Figure 3 The attached figure is a PFM morphology image of the molybdenum disulfide nanofiber piezoelectric material in Example 1.

[0028] Figure 4 The attached figure shows the butterfly loop of the molybdenum disulfide nanofiber piezoelectric material in Example 1.

[0029] Figure 5 The attached figure is the hysteresis curve of the molybdenum disulfide nanofiber piezoelectric material in Example 1. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Embodiment 1: This embodiment discloses a method for preparing a molybdenum disulfide nanofiber piezoelectric material, as follows:

[0032] (1) Weigh 1.00 g MoS2 powder and 1.00 g PVA powder in a ratio of 1:1 and grind and mix thoroughly;

[0033] (2) adding the mixed powder obtained in step (1) into 10.00 g of N-methylpyrrolidone (NMP) and heating and stirring at 120° C. for 2 h to obtain molybdenum disulfide gel;

[0034] (3) pouring the molybdenum disulfide gel obtained in step (2) into a mold made of an inorganic polymer colloidal material obtained by condensation of silicate, and cooling it in an environment of -25°C for more than 6 hours, so as to solidify the gel at low temperature and form a nanofiber material with a certain shape;

[0035] (4) placing the cooled molybdenum disulfide gel obtained in step (3) in an anhydrous ethanol solution for more than 6 hours to allow ethanol to displace NMP. This step is to remove NMP in the gel to avoid interference with subsequent treatments;

[0036] (5) placing the gel obtained in step (4) in deionized water for 24 hours to allow the deionized water to displace the ethanol, in order to further remove the organic solvent in the gel to obtain a purer nanofiber material;

[0037] (6) taking the supernatant after the replacement in step (5), pouring it into a centrifuge tube, and centrifuging it at 4000 rpm for 40 minutes to separate the impurities and unreacted raw materials in the nanofiber material by centrifugation;

[0038] (7) sonicating the solution after centrifugation in step (6) for 2 h to allow MoS2 to fully grow into the fiber knots. The key to this step is to utilize the oscillation effect of ultrasound to promote the uniform distribution and growth of MoS2 nanocrystals in the nanofibers;

[0039] (8) After ultrasonic treatment, the solution was taken out and the morphology of the MoS2 embedded in the fiber structure was clearly observed by TEM (see Appendix). Figure 1 ), the overall growth process is (Attached Figure 1 (a) MoS2 crystals enter the fiber and gradually move toward the fiber knot (attached Figure 1 (b)), and eventually all move into the fiber knot (attached Figure 1 (c, d)), by magnifying one of the black spheres, we can see the obvious hexagonal shape, which is the lattice stripes of 2H-MoS2 (attached Figure 1(e)). The material was prepared into a simple piezoelectric film sensor and tested in a sensor test system. Compared with the standard sensor, it showed good sensitivity without adding amplified charge and voltage (see Appendix Figure 2 ), with a sensitivity of 14.5mv / g. Then the material was tested with PFM, and a piezoelectric condensed structure appeared, with an obvious piezoelectric effect (see attached Figure 3 ,4,5), according to the butterfly curve, it can be calculated that the d33 of the MoS2 nanofiber material is about 188pm / V, the hysteresis loop shows good spontaneous polarization, and the hysteresis loop can also be used to analyze that the material is a single crystal piezoelectric material.

[0040] Embodiment 2: This embodiment discloses a method for preparing a molybdenum disulfide nanofiber piezoelectric material, as follows:

[0041] (1) Weigh 4.00 g MoS2 powder and 1.00 g PVA powder in a ratio of 4:1 and grind them thoroughly;

[0042] (2) adding the mixed powder obtained in step (1) into 10 g of N-methylpyrrolidone (NMP) and heating and stirring at 120° C. for 2 h to obtain molybdenum disulfide gel;

[0043] (3) pouring the molybdenum disulfide gel obtained in step (2) into a mold made of an inorganic polymer colloidal material obtained by condensation of silicate, and cooling it in an environment of -25°C for more than 6 hours, so as to solidify the gel at low temperature and form a nanofiber material with a certain shape;

[0044] (4) placing the cooled molybdenum disulfide gel obtained in step (3) in an anhydrous ethanol solution for more than 6 hours to allow ethanol to displace NMP. This step is to remove NMP in the gel to avoid interference with subsequent treatments;

[0045] (5) placing the gel obtained in step (4) in deionized water for 24 hours to allow the deionized water to displace the ethanol, in order to further remove the organic solvent in the gel to obtain a purer nanofiber material;

[0046] (6) taking the supernatant after the replacement in step (5), pouring it into a centrifuge tube, and centrifuging it at 4000 rpm for 40 minutes to separate the impurities and unreacted raw materials in the nanofiber material by centrifugation;

[0047] (7) sonicating the solution after centrifugation in step (6) for 2 h to allow MoS2 to fully grow into the fiber knots. The key to this step is to utilize the oscillation effect of ultrasound to promote the uniform distribution and growth of MoS2 nanocrystals in the nanofibers;

[0048] (8) The solution after ultrasound treatment is taken out, which is the prepared MoS2 nanofiber piezoelectric material.

[0049] Embodiment 3: This embodiment discloses a method for preparing a molybdenum disulfide nanofiber piezoelectric material, as follows:

[0050] (1) Weigh 6.00 g MoS2 powder and 1.00 g PVA powder in a ratio of 6:1 and mix thoroughly;

[0051] (2) adding the mixed powder obtained in step (1) into 10 g of N-methylpyrrolidone (NMP) and heating and stirring at 120° C. for 2 h to obtain molybdenum disulfide gel;

[0052] (3) pouring the molybdenum disulfide gel obtained in step (2) into a mold made of an inorganic polymer colloidal material obtained by condensation of silicate, and cooling it in an environment of -25°C for more than 6 hours, so as to solidify the gel at low temperature and form a nanofiber material with a certain shape;

[0053] (4) placing the cooled molybdenum disulfide gel obtained in step (3) in an anhydrous ethanol solution for more than 6 hours to allow ethanol to displace NMP. This step is to remove NMP in the gel to avoid interference with subsequent treatments;

[0054] (5) placing the gel obtained in step (4) in deionized water for 24 hours to allow the deionized water to displace the ethanol, in order to further remove the organic solvent in the gel to obtain a purer nanofiber material;

[0055] (6) taking the supernatant after the replacement in step (5), pouring it into a centrifuge tube, and centrifuging it at 4000 rpm for 40 minutes to separate the impurities and unreacted raw materials in the nanofiber material by centrifugation;

[0056] (7) sonicating the solution after centrifugation in step (6) for 2 h to allow MoS2 to fully grow into the fiber knots. The key to this step is to utilize the oscillation effect of ultrasound to promote the uniform distribution and growth of MoS2 nanocrystals in the nanofibers;

[0057] (8) The solution after ultrasound treatment is taken out, which is the prepared MoS2 nanofiber piezoelectric material.

[0058] Embodiment 4: This embodiment discloses a method for preparing a molybdenum disulfide nanofiber piezoelectric material, as follows:

[0059] (1) Weigh 8.00 g MoS2 powder and 1.00 g PVA powder in a ratio of 8:1 and grind and mix thoroughly;

[0060] (2) The mixed powder of step (1) was added to 10 g of N-methylpyrrolidone (NMP) and heated at 120 ° C with stirring for 2 h to obtain molybdenum disulfide gel;

[0061] (3) pouring the molybdenum disulfide gel obtained in step (2) into a mold made of an inorganic polymer colloidal material obtained by condensation of silicate, and cooling it in an environment of -25°C for more than 6 hours, so as to solidify the gel at low temperature and form a nanofiber material with a certain shape;

[0062] (4) placing the cooled molybdenum disulfide gel obtained in step (3) in an anhydrous ethanol solution for more than 6 hours to allow ethanol to displace NMP. This step is to remove NMP in the gel to avoid interference with subsequent treatments;

[0063] (5) placing the gel obtained in step (4) in deionized water for 24 hours to allow the deionized water to displace the ethanol, in order to further remove the organic solvent in the gel to obtain a purer nanofiber material;

[0064] (6) taking the supernatant after the replacement in step (5), pouring it into a centrifuge tube, and centrifuging it at 4000 rpm for 40 minutes to separate the impurities and unreacted raw materials in the nanofiber material by centrifugation;

[0065] (7) sonicating the solution after centrifugation in step (6) for 2 h to allow MoS2 to fully grow into the fiber knots. The key to this step is to utilize the oscillation effect of ultrasound to promote the uniform distribution and growth of MoS2 nanocrystals in the nanofibers;

[0066] (8) The solution after ultrasound treatment is taken out, which is the prepared MoS2 nanofiber piezoelectric material.

[0067] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a molybdenum disulfide nanofiber piezoelectric material, characterized in that: The composite solution of molybdenum disulfide nanofiber piezoelectric material is prepared by using polyvinyl alcohol, molybdenum disulfide, N-methylpyrrolidone, anhydrous ethanol and deionized water as raw materials through solution replacement.

2. The molybdenum disulfide in the molybdenum disulfide nanofiber composite solution according to claim 1 is a two-dimensional powder material with a diameter of 100 nm. The preparation method of the molybdenum disulfide nanofiber composite solution is as follows: (1) mixing molybdenum disulfide powder and polyvinyl alcohol (PVA) powder uniformly by ball milling in a ratio of 1:1 to 8:1; (2) adding the mixed powder of step (1) into N-methylpyrrolidone (NMP), heating and stirring at 120° C. for 2 h, wherein the mass ratio of NMP to PVA is 10:1, to obtain molybdenum disulfide gel; (3) pouring the molybdenum disulfide gel obtained in step (2) into a mold made of an inorganic polymer colloidal material obtained by condensation of silicate, and cooling it in an environment of -25°C for more than 6 hours, so as to solidify the gel at low temperature and form a nanofiber material with a certain shape; (4) placing the cooled molybdenum disulfide gel obtained in step (3) in an anhydrous ethanol solution for more than 6 hours to allow ethanol to displace NMP. This step is to remove NMP in the gel to avoid interference with subsequent treatments; (5) placing the gel obtained in step (4) in deionized water for 24 hours to allow the deionized water to displace the ethanol, in order to further remove the organic solvent in the gel to obtain a purer nanofiber material; (6) taking the supernatant after the replacement in step (5), pouring it into a centrifuge tube, and centrifuging it at 4000 rpm for 40 minutes to separate the impurities and unreacted raw materials in the nanofiber material by centrifugation; (7) sonicating the solution after centrifugation in step (6) for 2 h to allow the MoS2 nanocrystals to fully grow into the fiber knots. The key to this step is to utilize the oscillation effect of ultrasound to promote the uniform distribution and growth of MoS2 nanocrystals in the nanofibers; (8) The solution after ultrasound was taken out and observed by TEM. The obvious fiber structure embedded in the quantum morphology can be observed. The material was used to prepare a simple piezoelectric film sensor and the piezoelectric coefficient d was obtained by testing. 33 It is about 345pC / N; PFM test on this material shows good piezoelectric domain structure and obvious piezoelectric effect; test in sensor test system shows good sensitivity.

3. The method for preparing a molybdenum disulfide nanofiber piezoelectric material according to claim 1, characterized in that: The molybdenum disulfide 1g, polyvinyl alcohol powder 1g, N-methylpyrrolidone 10ml.